2023
DOI: 10.3390/cells12141856
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold-Based (Matrigel™) 3D Culture Technique of Glioblastoma Recovers a Patient-like Immunosuppressive Phenotype

Abstract: Conventional 2D cultures are commonly used in cancer research though they come with limitations such as the lack of microenvironment or reduced cell heterogeneity. In this study, we investigated in what respect a scaffold-based (Matrigel™) 3D culture technique can ameliorate the limitations of 2D cultures. NGS-based bulk and single-cell sequencing of matched pairs of 2D and 3D models showed an altered transcription of key immune regulatory genes in around 36% of 3D models, indicating the reoccurrence of an imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Evidence of this was also provided in a recent characterization of the used 3D models by Braun et al. describing core region with necrotic and damaged cells, similar to tumors from GBM patients ( 11 ). In addition to the necrotic areas of these complex models, it was observed that an outer layer with proliferating cells circumscribed the organoid.…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Evidence of this was also provided in a recent characterization of the used 3D models by Braun et al. describing core region with necrotic and damaged cells, similar to tumors from GBM patients ( 11 ). In addition to the necrotic areas of these complex models, it was observed that an outer layer with proliferating cells circumscribed the organoid.…”
Section: Discussionmentioning
confidence: 62%
“…Since in 3D organoids, cells in the core of the cell aggregate may have reduced access to essential nutrients, hypoxia and nutrient deficiency might trigger stress responses (74). Evidence of this was also provided in a recent characterization of the used 3D models by Braun et al describing core region with necrotic and damaged cells, similar to tumors from GBM patients (11). In addition to the necrotic areas of these complex models, it was observed that an outer layer with proliferating cells circumscribed the organoid.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations